2017
DOI: 10.21608/ejnf.2017.75326
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nano-Silver Particles Supplementation in Drinking Water on Performance and Intestinal Micro-Flora Population of Growing Poultry

Abstract: hree experiments were conducted to investigate the effects of drinking water supplementation with 0, 5 and 10 ppm of Nano-silver particles (AgNPs) / liter on performance, carcass characteristics and gut micro-flora population of grower rabbits from 63 to 91day of age, broiler chicks from 1 to 42 day of age and grower Japanese quails from 7 to 42 days of age. Results showed that, different levels of AgNPs in drinking water hadn't any significant effect on body weight, body weight gain (BWG) or feed conversion r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…Numerically, the chicks received drinking water supplemented with 10.0 ppm nanoparticles had the highest percentages of carcass, TEP and abdominal fat% which recorded values (70.34, 75.03 and 1.35%) respectively compared with other treatments. These results agree with Ibrahim et al (2015), El-Faham et al (2017) who showed that the percentages of Dressing percentage and adipose fat hadn't affected significantly with treatments.…”
Section: Resultssupporting
confidence: 92%
“…Numerically, the chicks received drinking water supplemented with 10.0 ppm nanoparticles had the highest percentages of carcass, TEP and abdominal fat% which recorded values (70.34, 75.03 and 1.35%) respectively compared with other treatments. These results agree with Ibrahim et al (2015), El-Faham et al (2017) who showed that the percentages of Dressing percentage and adipose fat hadn't affected significantly with treatments.…”
Section: Resultssupporting
confidence: 92%
“…In the same context in rats, Kim et al (2010) reported that oral consumption of Ag-NPs did not significantly affect liver %, spleen %, kidney %, and heart %. El-Faham et al (2017) observed no significant changes in carcass traits of quail, broilers, and rabbits that were administered in drinking water with various levels of Ag-NPs (0, 5, or 10 ppm). The converse trend was detected by Hassan (2018), who supplemented drinking water or feed of broilers with Ag-NPs and documented a significant change in dressing %, liver %, and heart %.…”
Section: Discussionmentioning
confidence: 86%
“…Also, the possible causes of the inconsistent results can be related to the difference in animal species, the size of particles, the technique of synthesis, the administration dose, or manners. (El-Faham et al, 2017) found that different levels of Ag-NPs (0, 5, or 10 ppm in the drinking water) did not yield any statistically significant impact on LBW, BWG, or FCR of rabbits and broilers. However, it was observed that the Japanese quails exhibited superior BWG and FCR values in the group supplemented with 10 ppm of Ag-NPs, in comparison to the control group.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The results showed that significantly decreasing in LBW increase the silver nanoparticles levels. El-Faham et al (2017) studied the effect of different levels of silver nanoparticles (0.0, 5.0 and 10 ppm/l) in poultry (broiler chicken, rabbits and Jap. quail) drinking water on performance.…”
Section: Introductionmentioning
confidence: 99%